Gilead Sciences and Sovaldi : the cost of a cure (A) - Budish, Benjamin (SAGE Knowledge. Cases., 2017)
Gilead Sciences hepatitis C drug, Sovaldi, proved more effective than the competition and was priced in line with market conditions. However, extremely high cost and large patient population captured the attention of the media, the public, NGOs, and even the government. The controversy deepened when the company revealed the cost in developing countries would be roughly 1% of the cost in the U.S.